Alternatif Pidana dalam Penyelesaian Sengketa Perbankan Syariah di Indonesia - Hidayah, Phani Annisatul (Masyarakat Ekonomi Syariah Bogor, 2024)
The objective of this text is to understand how conflicts are resolved within the realm of Islamic banking and to devise effective solutions. One prevalent challenge is the occurrence of conflicts or disputes within Islamic banks, which are at times inadequately resolved. The problem statement in this research revolves around criminal activities and dispute resolution within the Islamic banking sector. The research methodology used is qualitative, employing the literature review method or library research. The study findings highlight the significant role of Islamic banking in Indonesia across various domains, especially in the financial activities of communities and the economy, catering to individual needs. Nonetheless, operational difficulties may lead to potential conflicts or disputes. These disputes typically require resolution from both parties involved, namely the bank and the customer, as they share equal roles as stakeholders. Two dispute resolution methods have been identified within Islamic banking: litigation (in court) and non-litigation (outside court). This study identifies the challenges arising in Indonesian Islamic banking and proposes solutions to mitigate them. The two dispute resolution methods suggested by the researchers can be used to overcome challenges in Islamic banking, although each method has its own advantages and disadvantages each approach comes with its own strengths and weaknesses.